Determining the need for team-based training in delirium management: A needs assessment of surgical healthcare professionals. Issue 6 (3rd November 2015) - Sockalingam, Sanjeev; Tehrani, Hedieh; Kacikanis, Anna; Tan, Adrienne; Hawa, Raed; Anderson, Ruthie; Okrainec, Allan; Abbey, Susan
Abstract: The high incidence of delirium in surgical units is a serious quality concern, given its impact on morbidity and mortality. While successful delirium management depends upon interdisciplinary care, training needs for surgical teams have not been studied. A needs assessment of surgical units was conducted to determine perceived comfort in managing delirium, and interprofessional training needs for team-based care. We administered a survey to 106 General Surgery healthcare professionals (69% response rate) with a focus on attitudes towards delirium and team management. Although most respondents identified delirium as important to patient outcomes, only 61% of healthcare professionals indicated that a team-based approach was always observed in practice. Less than half had a clear understanding of their role in delirium care, while just over half observed team communication of delirium care plans during handover. This is the first observation of clear gaps in perceived team performance in a General Surgery setting.